Inauguration of SMU-TCS iCity Laboratory - Singapore Management University (Institutional Knowledge at Singapore Management University, 2012)
The Singapore Management University (SMU) and Tata Consultancy Services (TCS), a leading IT services, business solutions and consulting firm, inaugurated the SMU-TCS Intelligent City Laboratory (“iCity Lab”) on 9 May 2012 (Wednesday). The inauguration ceremony was held at the iCity Lab Experience Centre located at the SMU School of Information Systems (SIS). Equipped with interactive technology, this Experience Centre will serve as a venue for city managers and urban planners to experience the new ideas and technologies which the Lab will be developing. This collaboration initiative was announced on 5 August 2011, which aimed to develop, as well as establish industry standards and IT frameworks for the emerging intelligent city model of urban development. The SMU-TCS iCity Lab is focused on harnessing technology and develop solutions to put people at the centre of city management.